ACTIVITY, STABILITY TESTS AND SCREENING CRYSTALLIZATION CONDITIONS OF MUTANTS RECOMBINANT MANGANESE SUPEROXIDE DISMUTASE Staphylococcus equorum - Muliadi, Rahmat
Recombinant Manganese Superoxide Dismutase Staphylococcus equorum (rMnSODSeq) in its native form has good stability over a wide pH range and high temperature. Native rMnSODSeq is relatively unstable in long-term UVC exposure so it is engineered into several mutants including G125N, S126C, L169W and G125T. This research aimed to study the effect of G125T, G125N, S126C and L169W substitutions on their activity and stability as well as crystallization conditions. The screening of crystallization condition of rMnSODSeq mutants was carried out as a first step to determine their three-dimensional structure. The research was initiated with isolation and confirmation of mutants by migration, restriction and nucleotide sequencing analyzes. Protein overproduction was carried out at 37°C for 4 hours by induction with isopropyl ?-D-1- thiogalactopiranoside (IPTG) 1 mM. Purification of proteins was carried out by Ni 2+ -NTA affinity chromatography. Protein activity was analyzed qualitatively and quantitatively by zimography and colorimetric methods. Protein stability was tested against UVC exposure and temperature variations. The screening of protein crystallization was carried out using the hanging drop method. The results indicate a decrease in the specific activity of G125N, S126C, L169W and G125T were 989 U / mg, 571 U / mg, 450 U / mg and 62 U / mg, respectively. The mutants displayed better stability against long term UVC exposure and temperature. The residual activity of G125N, S126C, L169W and G125T after exposure at 90 ° C was 78.6%; 65.9%; 63.7% and 62.1% while the residual activity after UVC exposure for 60 minutes the activity was 79%; 78%; 76% and 73% respectively based on the initial activity each mutant. The optimum crystallization conditions of G125T and S126C were obtained in a mixture of 20% PEG 600 solution, Tris-HCl 0.1 M pH 7.4. The composition of mother liquor S126C are combination of 10% PEG 600 and 10% PEG 4000, Tris-HCl 0.1 M pH 7.4 and a protein concentration of 8 mg/ml with 4 µL droplet volume. Optimal crystallization conditions for the L169W cannot be determined yet. The substitution of G125T, S126C, L169W and G125N on rMnSODSeq affect the protein crystallization condition.